What inspires students to become entrepreneurs? The Influence of Attitude, Subjective Norms, Self-Efficacy, Locus of Control, and Environmental Support on Entrepreneurial Intention - Elissa Dwi Lestari; Nosica Rizkalla; Aurel Timothius Tan (Profesional Muda Cendekia Publishing, 2023)
Indonesia currently has a high rate of educated unemployment. Because most college graduates are still oriented toward being job seekers rather than job creators, there is a high rate of educated unemployment. As a result, the purpose of this study was to identify factors that influence student entrepreneurial intentions in terms of the Theory of Planned Behavior framework (attitude toward entrepreneurship and subjective norms), which is supplemented with personality variables (self-efficacy and locus of control) and environmental variables in the form of environment support. The study was conducted quantitatively with judgmental sampling of 108 students who are still enrolled in school, have participated in education or entrepreneurship programs, and do not own a business. Multiple regression was used to analyze the study's findings.